Swarm inspired test case generation for online C++ programming assessment - Foong, O.-M. (Institute of Electrical and Electronics Engineers Inc., 2014)
It is time consuming for lecturers to manually compile, run and verify students' programming assignments. Moreover, they also need to define test cases for different programming exercises in order to assess students' code. This paper presents a swarm inspired automatic test case generation for Online Programming Assessment or Judge (UOJ) system. The UOJ is built with the purpose to assist lecturers in evaluating codes submitted from students and generate test cases for every programming problem automatically. It also helps students to practice and enhance their programming skills. In this study, the mechanism of automatic test case generation was explored using Particle Swarm Optimization (PSO) algorithm and new fitness function is proposed to determine the optimal solution for each problem. Experiments were set up to benchmark between manual and automatic PSO test case generation results to evaluate the efficiency of the proposed method. The preliminary results are satisfactory for automatic test case generation using swarm inspired PSO algorithm in C++ programming assignments. Â© 2014 IEEE.